2018
DOI: 10.1016/j.bioorg.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the N-terminal processing of human interferon α-2b and its chimeric derivatives expressed in Escherichia coli

Abstract: We have previously shown that human interferon α-2b (IFN) produced in Escherichia coli (E. coli) is heterogeneous at the N-terminal, with three major species (Ahsan et al., 2014). These are: (a) the direct translation product of the gene retaining the N-terminal methionine, (b) a species from which the methionyl residue has been removed by E. coli methionyl aminopeptidase to give the native interferon α-2b and (c) in which the N-terminal Cys residue of the latter contains an acetyl group. In this paper we over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this context, we also analyzed their dependence on their most direct regulator (glucose) and some direct effectors (deacetylase CobB, peptidyl N(ε)-Lysine acetyl-transferase PatZ). Although this topic belongs to the ambit of molecular physiology, the clarification of these mechanisms could have important consequences in the field of biotechnological applications (Kuczynska-Wiśnik et al, 2016 ; Ahsan et al, 2017 ; Basak et al, 2017 ; Ishigaki et al, 2017 ; Venkat et al, 2018 ), and even for some medical issues (Bernal et al, 2016 ; Ou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we also analyzed their dependence on their most direct regulator (glucose) and some direct effectors (deacetylase CobB, peptidyl N(ε)-Lysine acetyl-transferase PatZ). Although this topic belongs to the ambit of molecular physiology, the clarification of these mechanisms could have important consequences in the field of biotechnological applications (Kuczynska-Wiśnik et al, 2016 ; Ahsan et al, 2017 ; Basak et al, 2017 ; Ishigaki et al, 2017 ; Venkat et al, 2018 ), and even for some medical issues (Bernal et al, 2016 ; Ou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that acetylation could occur at N-terminal Cys residue in IFNα2b, and the acetylated form had only 10% of the activity of native molecule [17]. To overcome this N-terminal heterogeneity, many strategies have been developed, such as engineered interferon derivatives with phenylalanine residue directly downstream of the N-terminal Met [20], and co-expression of engineered MetAP in E. coli [14].…”
Section: Discussionmentioning
confidence: 99%